2014
DOI: 10.1038/npp.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from the Expectable Environment in Early Childhood and Emerging Psychopathology

Abstract: Current frameworks for understanding the link between early adverse childhood experiences and later negative life outcomes, including psychopathology, focus on the mediating negative impact on brain and biological systems in the developing child resulting broadly from stress and trauma. Although this approach is useful, we argue that the framework could be functionally extended by distinguishing the effects of two different types of abnormal input, both deviations from the expectable environment in early child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 190 publications
(185 reference statements)
7
183
0
Order By: Relevance
“…First, although we used careful coding systems to evaluate the cumulative effects of objectively rated ELS severity on corticolimbic development, we use the term ELS broadly to include multiple forms of adverse childhood experiences, ranging from maltreatment and neglect to residential moves and exposure to marital disagreements. As we noted above, researchers have suggested that different forms of early adverse experiences have different psychobiological consequences (Humphreys & Zeanah, 2015; McLaughlin & Sheridan, 2016; Teicher & Samson, 2016; Teicher, Samson, Anderson, & Ohashi, 2016). Future research should examine the differential effects of types of stress exposure, including exposure to threat and neglect, on neural functioning.…”
Section: Discussionmentioning
confidence: 83%
“…First, although we used careful coding systems to evaluate the cumulative effects of objectively rated ELS severity on corticolimbic development, we use the term ELS broadly to include multiple forms of adverse childhood experiences, ranging from maltreatment and neglect to residential moves and exposure to marital disagreements. As we noted above, researchers have suggested that different forms of early adverse experiences have different psychobiological consequences (Humphreys & Zeanah, 2015; McLaughlin & Sheridan, 2016; Teicher & Samson, 2016; Teicher, Samson, Anderson, & Ohashi, 2016). Future research should examine the differential effects of types of stress exposure, including exposure to threat and neglect, on neural functioning.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, to find that hypocortisolism served as a mediator of externalizing problems is consistent with previous work and might suggest that it is part of the neurobiological pathway to some aspects of externalizing behavior. ADHD symptoms are very commonly reported among children who have experienced deprivation early in life, particularly those reared in poor quality institutional settings (Humphreys & Zeanah, 2015). Nonetheless, there is little evidence that hypocortisolism is a part of the pathophysiology of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…As I have argued elsewhere (McLaughlin, Sheridan, & Lambert, 2014; Sheridan & McLaughlin, 2014), deviations from the expectable environment often take two primary forms: an absence of expected inputs (e. g., limited exposure to language or the absence of a primary caregiver), or the presence of unexpected inputs that represent significant threats to the physical integrity or well-being of the child (e.g., exposure to violence). A similar approach to classifying key forms of child adversity has been articulated by others as well (Farah et al, 2008; Humphreys & Zeanah, 2015). These experiences can either be chronic (e.g., prolonged neglect) or involve single events that are severe enough to represent a deviation from the expectable environment (e.g., sexual abuse).…”
Section: Future Directions In Childhood Adversity and Youth Psychopatmentioning
confidence: 91%